THE ROLE OF INTERNET ANALYTICS IN IMPROVING THE EFFICIENCY OF MARKETING ACTIVITIES - Жук, Оксана (SWorldJournal, 2025)
This study examines how the digital transformation of business has led to an increased role of web analytics in marketing decision-making. Modern enterprises employ analytical tools to optimize advertising campaigns, improve communication efficiency, and